Snake Venom, A Natural Library of New Potential Therapeutic Molecules: Challenges and Current Perspectives - Simoes Silva, Rodrigo (2018)
Background: Research involving snake venom has gradually surpassed the simple discovery of new molecules using purification and structural characterization processes, and extended to the identification of their molecular targets and the evaluation of their therapeutic potential. Nevertheless, this only became possible due to constant progress in experimental biology and protein purification approaches. Objective: This review aims to discuss the main components of snake venoms that have been investigated for biotechnological purposes, and to discover how these promising biomolecules were obtained with the satisfactory degree of purity that have enabled such studies. Advances in purification technologies of various snake venom molecules have allowed for important discoveries of proteins and peptides with different biomedical and biotechnological applications. Result and Conclusion: It is believed that significant experimental and computational advances will arise in similar proportions in the coming years that will allow researchers to map the molecular regions responsible for their pharmacological actions, their respective mechanisms of action and their cell targets.